Implementation of Competency-Based Curriculum in Improving the Quality of Education in Schools - Yohanna Lature; Lestari Waruwu; Lenis Mahayati Waruwu; Cisrad Anda Nita Zalukhu (Journal of Computer Science Advancements, 2024)
The aim of this research is to evaluate Curriculum Effectiveness: Understanding the extent to which a competency-based curriculum can improve the quality of education by measuring student learning outcomes, level of mastery of material, and students' ability to apply the knowledge and skills they learn. This research uses qualitative/quantitative methods with a descriptive approach. Some of the instruments used in this research are student portfolios, practical exams, formative assessments. The researcher's data collection techniques used interviews, questionnaires, classroom observations, classroom observations, document analysis, exams and assessments, focus group discussions, and reflective notes. This research shows that the implementation of Competency-Based Curriculum (KBK) in the context of school education requires the active involvement of teachers in preparing more contextual learning that is oriented towards skills development. Students are expected to become successful, honest, disciplined, and responsible individuals. However, the quality of education in Indonesia still requires many improvements, including the implementation of appropriate policies as an alternative solution to educational problems. Relevant KBK programs with initiatives for training education personnel include participation in various places, development of family planning organizations, and utilizing the education process to address educational gaps. The importance of administrative support, resource availability, and continuous evaluation and assessment are key to the successful implementation of KBK. Parental and community involvement are also crucial in supporting the implementation of KBK, which ultimately positively impacts the quality of education, student motivation, and alignment with local needs.